Política municipal de segurança alimentar e nutricional: o caso de Marechal Cândido Rondon, PR - Amarante, Eliane Aparecida Laiol do (2019)
The present study advocated to show what strategies were adopted to implement the municipal school feeding policy of the municipality of Marechal Cândido Rondon - PR. The objective of this study was to analyze the factors that contributed to the construction of a municipal plan for the acquisition of organic or agroecological food for the National School Feeding Program - PNAE, in the form of public purchases. The research was carried out through a qualitative and quantitative analysis of documents related to the elaboration of the Municipal Food and Nutrition Security Plan - PLAMSAN and Law 4.904 / 16, in addition to the application of a semistructured questionnaire, which allowed to know those involved in the development of these documents, and was developed from interviews with open and closed questions directed to municipal public managers (mayor, health secretaries, agriculture, education, culture, directors and pedagogical guides of all municipal schools, municipal education councilors and councilors involved in the approval of said law). To complete the research, the socioeconomic characterization of 35 families of agroecological farmers of the municipality was carried out. The results indicate that the municipal policy of SAN strengthens the family agriculture and confers public recognition in the form of the law stimulating the agroecological and organic production simultaneously guarantees the SAN of the children, served by the municipal education network.